Today Ecological Guarantees, Yesterday Social Guarantees - Quesada, Gabriel (2003)
Costa Rica is a country of great ecological and human wealth due to its location and physical characteristics as it is located between two continental masses, North America and South America; the country has a rich biodiversity of continental, migratory, and endemic species. On a human level, the situation is no different. Costa Rica has been both the southern border of Mesoamerica and the northern border of South America. Different aboriginal groups inhabited our lands, enriching our cultural and ethnic diversity.